2017
DOI: 10.1080/10640266.2017.1364934
|View full text |Cite
|
Sign up to set email alerts
|

Telephone helplines as a source of support for eating disorders: Service user, carer, and health professional perspectives

Abstract: Access to care for eating disorders can be problematic for numerous reasons including lack of understanding and delays with treatment referrals. Previous research has highlighted the benefits of telephone helplines as an accessible source of support for those who may not wish to access face-to-face support or to fill a gap for those waiting for treatment. This study aimed to gain an insight into the perspectives of those who may use or refer others to a telephone helpline in order to identify the requirements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Previous research about an eating disorders helpline noted that those affected by anorexia nervosa and bulimia nervosa were interested in counselling, whilst those affected by binge eating disorder sought emotional support [ 44 ]. Eating disorder helplines can also serve as a first step, in parallel to treatment, or as an extension of this support when in recovery and helplines may provide an outlet for carers to access information and discuss their own experiences, while supporting their family member [ 45 ]. A recent evaluation carried out on behalf of support organisation, Beat, in the United Kingdom, found that its helpline helped service users understand their eating disorder better, reduced feelings of isolation and prompted them to act, such as contacting a doctor or read more information [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research about an eating disorders helpline noted that those affected by anorexia nervosa and bulimia nervosa were interested in counselling, whilst those affected by binge eating disorder sought emotional support [ 44 ]. Eating disorder helplines can also serve as a first step, in parallel to treatment, or as an extension of this support when in recovery and helplines may provide an outlet for carers to access information and discuss their own experiences, while supporting their family member [ 45 ]. A recent evaluation carried out on behalf of support organisation, Beat, in the United Kingdom, found that its helpline helped service users understand their eating disorder better, reduced feelings of isolation and prompted them to act, such as contacting a doctor or read more information [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Helplines have been used for many years in different settings, such as suicidal crisis [13], cancer [14], chronic rheumatic diseases [15], eating disorders [16], or substance use disorders [17]. Helplines and real-time chat for problem gambling have been implemented and assessed in several countries [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, a permanência da pessoa em sofrimento mental no seio familiar é uma questão muito discutida e envolta por preocupações. Nesse sentido, é importante considerar que existem desgastes e exigências que as famílias não foram preparadas para assumir e sustentar por muito tempo (PRIOR et al, 2018) Quando se compreende que o familiar cuidador é um co-participante do processo de cuidado passa-se a considerar a necessidade tanto de integrá-lo a uma política formal de cuidado por parte dos profissionais de saúde quanto também oportunizar cuidados a esse público ainda bastante invisibilizado nesse contexto.…”
Section: Resultsunclassified